Autoimmune Polyglandular Syndrome Type-2 A Case Report on a Rare Disease - Hassan, Wahaj Ul; Farid, Ummarah Zafar; Ali, Kamran; Naseer, Umer (Pakistan Armed Forces Medical Journal, 2023)
Autoimmune polyglandular syndromes (APS) are rare disorders involving multiple endocrine and non-endocrine organs. These are often difficult to diagnose, as the clinical presentation of these is insidious. We present a case where a 29-year-old man presented to the Emergency Department in a state of altered sensorium with a history of focal seizures. His clinical presentation further included hypotension, malaise, and diplopia. A detailed workup revealed multiple endocrine gland involvement, and a diagnosis of APS was made.